Welfare Magnets, Taxation and the Location Decisions of Migrants to the EU - Klaus Nowotny (European Regional Science Association (ERSA), 2011)
Migrants are among the groups most vulnerable to economic fluctuations. As predicted by the 'welfare magnet' hypothesis, migrants can therefore be expected to–ceteris paribus–prefer countries with more generous welfare provisions to insure themselves against labor market risks. This paper analyzes the role of the welfare magnet hypothesis for migrants to the EU-15 at the regional level. The empirical analysis based on a random parameters logit model shows that the regional location decisions of migrants are mostly governed by income opportunities, labor market conditions, ethnic networks and a common language. There is no strong evidence for the welfare magnet hypothesis in the EU, but the empirical model shows that the design of the (income) tax system has a large and consistent effect on locational choice.
Keywords: 330